Synthesis of novel magnetic adsorbents from coffee husks by hydrothermal carbonization - Hien, Tran Thi; Vu, Nguyen The; Thien, Pham Huu; Thanh, Nguyen Dinh; Tuan, Phan Dinh (Vietnam Journal of Science and Technology, 2017)
Coffee husks are transformed into magnetic adsorption materials by the hydrothermal carbonization (HTC) method at low temperature (453 K) in the presence of iron (III) salt. For the capability of absorbing methylene blue, the absorbed content by biochar is 105.831 mg/g and by magnetic adsorption material is 263.158 mg/g. Absorption capacity are also described through isotherm Langmuir model. HTC can be seen as an alternative and effective approach in converting waste biomass into materials for wastewater treatment.